2016
DOI: 10.18632/oncotarget.8892
|View full text |Cite
|
Sign up to set email alerts
|

Correlational study on mitochondrial DNA mutations as potential risk factors in breast cancer

Abstract: The presented study performed an mtDNA genome-wide association analysis to screen the peripheral blood of breast cancer patients for high-risk germline mutations. Unlike previous studies, which have used breast tissue in analyzing somatic mutations, we looked for germline mutations in our study, since they are better predictors of breast cancer in high-risk groups, facilitate early, non-invasive diagnoses of breast cancer and may provide a broader spectrum of therapeutic options. The data comprised 22 samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 25 publications
4
19
1
Order By: Relevance
“…A previous study reported 170 mtDNA mutations in 22 samples from a healthy cohort,21 and the average frequency of mtDNA germline mutations was similar to our results. Three mtDNA mutations in the present cases were observed in mitochondrial haplogroup D4f1.…”
Section: Discussionsupporting
confidence: 92%
“…A previous study reported 170 mtDNA mutations in 22 samples from a healthy cohort,21 and the average frequency of mtDNA germline mutations was similar to our results. Three mtDNA mutations in the present cases were observed in mitochondrial haplogroup D4f1.…”
Section: Discussionsupporting
confidence: 92%
“…One of the most widely studied mitochondrial SNPs is G10398A. Related studies reported that 10398A was associated with some systemic diseases, increasing the risk of Parkinson's disease, breast cancer, and other types (Chia‐Wei et al, ; Gui et al, ; Juo et al, ; Li et al, ; Mims et al, ; van der Walt et al, ). A recent study showed that cognitive decline was not related to any usual risk factor but to the G allele of A10398G in mtDNA (Monte et al, ), and another study suggested that the mitochondrial DNA 10398 A/G polymorphism plays a possible role in the genetic etiology of attention deficit hyperactivity disorder (ADHD) in Korean children (Hwang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The clinical phenotypes associated with the G8701A polymorphism have been reported to include hereditary optic neuropathy, mitochondrial encephalomyopathy, Parkinson's syndrome, deafness, and metabolic syndrome; of these, deafness was identified in a pedigree study (Chalkia et al, ; Li, Zhang, Li, & Wang, ; Martikainen et al, ; Mkaouar‐Rebai, Tlili, Masmoudi, Charfeddine, & Fakhfakh, ). The A8860G polymorphism has been detected in many diseases, but evidence for its association with these diseases is not strong (Bahreini, Houshmand, Modarressi, & Akrami, ; Chia‐Wei et al, ; Li et al, , ; Masserrat et al, ). Some authors found that A8860G may reduce the stability of ATPase6 (Houshmand et al, ), but another study suggested that it is a benign point mutation with no effect on protein function (Masserrat et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A pro-oncogenic state may not only be favored by mtDNA mutations or the haplotype but also by mtDNA polymorphisms. This has been shown for single nucleotide polymorphisms (SNPs) in the D-loop (colorectal adenoma) [Thyagarajan et al, in press], the tRNA(Ile) gene (colorectal cancer) [Kumar et al, 2017], COX genes (hepatocellular carcinoma) [Wang et al, in press], and in COX1, COX2, ND5, and ATP6 genes respectively (breast cancer) [Li et al, 2016].…”
mentioning
confidence: 99%